2018
DOI: 10.1016/j.jhep.2017.12.018
|View full text |Cite
|
Sign up to set email alerts
|

AXIN deficiency in human and mouse hepatocytes induces hepatocellular carcinoma in the absence of β-catenin activation

Abstract: Liver cancer has a poor prognosis. Defining the molecular pathways involved is important for developing new therapeutic approaches. The Wnt/β-catenin pathway is the most frequently deregulated pathway in hepatocellular carcinoma (HCC). Mutations of AXIN1, a member of this pathway, represent about 10% of HCC mutations. Using both human HCC collections and engineered mouse models of liver cancers with AXIN1 mutation or deletion, we defined a common signature of liver tumors mutated for AXIN1 and demonstrate that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
94
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 90 publications
(104 citation statements)
references
References 46 publications
8
94
2
Order By: Relevance
“…A previous study suggests that Notch pathway is activated in AXIN1 mutant human HCC . Consistent with this report, our global gene expression analysis revealed the activation of Notch signaling in c‐Met/sgAxin1 HCC samples (Fig.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…A previous study suggests that Notch pathway is activated in AXIN1 mutant human HCC . Consistent with this report, our global gene expression analysis revealed the activation of Notch signaling in c‐Met/sgAxin1 HCC samples (Fig.…”
Section: Resultssupporting
confidence: 91%
“…Intriguingly, several studies revealed the lack of expression of liver‐specific Wnt/β‐Catenin target genes, such as GS, in human and mouse HCCs harboring AXIN1 mutations . Using gene expression analysis, a recent study by Abitbol et al suggested that CTNNB1 mutant human HCCs showed strong or weak Wnt/β‐Catenin activation, whereas more than 70% of AXIN1 mutant HCCs belonged to the “no activation” subgroup . All these data suggest that AXIN1 might function through Wnt/β‐Catenin‐independent mechanisms along hepatocarcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Axin1 deletion does not lead to β-catenin activation in these tumours24 (online supplementary figure SI1D). Axin1 -HCC exhibited the Warburg effect, with decreased glucose oxidation and increased lactate production (online supplementary figure SI2A).…”
Section: Resultsmentioning
confidence: 90%
“…We experimentally validated these data by characterising the metabolic reprogramming of tumours developed in a model in which HCC is induced following the deletion of Axin1 in hepatocytes, called Axin1 -HCC 24 . Axin1 deletion does not lead to β-catenin activation in these tumours24 (online supplementary figure SI1D).…”
Section: Resultsmentioning
confidence: 95%